2000
DOI: 10.1002/1097-4598(200012)23:12<1887::aid-mus16>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal motor neuropathy presenting with respiratory failure

Abstract: Multifocal motor neuropathy is a disorder characterized by slowly progressive asymmetrical limb weakness and multiple motor conduction blocks. We report a 56‐year‐old woman with this disorder who presented unusually with respiratory failure and who initially had absent responses to phrenic nerve stimulation bilaterally. The mechanism of the patient's respiratory failure may have been chronic conduction blocks in the phrenic nerves leading to diaphragmatic weakness. © 2000 John Wiley & Sons, Inc. Muscle Nerve 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…12 It is believed that respiratory failure may be due to chronic conduction blocks in the phrenic nerves and possible axonal damage, which is not rare in the course of CIDP. 11,13 In the literature, a pathologic study of one case who died of ventilatory failure revealed extensive areas of ongoing demyelination and remyelination associated with axonal loss in the phrenic nerve. 5 Dyck et al also noted segmental demyelination with and without hypertrophic changes in 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…12 It is believed that respiratory failure may be due to chronic conduction blocks in the phrenic nerves and possible axonal damage, which is not rare in the course of CIDP. 11,13 In the literature, a pathologic study of one case who died of ventilatory failure revealed extensive areas of ongoing demyelination and remyelination associated with axonal loss in the phrenic nerve. 5 Dyck et al also noted segmental demyelination with and without hypertrophic changes in 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Life expectancy in MMN is normal but conversely spontaneous remission has not been reported 1,5,40. Life-threatening respiratory weakness associated with hypoventilation and respiratory insufficiency due to phrenic nerve involvement with diaphragmatic paresis has been described but is thought to be a rare manifestation of MMN 13,15…”
Section: Natural Historymentioning
confidence: 99%
“…Impairment is mainly in the upper limb function but, with progression of the disease, there can be a more generalized impact. Cranial nerve impairment is rare 12,13,84. Somewhat surprisingly, sensory symptoms such as pain and dysesthesia are not uncommon.…”
Section: Patient Focused Perspectivesmentioning
confidence: 99%
“…Prior reports describing phrenic involvement in the setting of multifocal motor neuropathy 6 led us to treat three of our patients with IV Ig. We found it difficult to exclude this potentially treatable disorder based solely on our clinical and electrophysiological findings since it may present focally 7 and because it is not possible to demonstrate conduction block by stimulating the phrenic nerve at only a single point.…”
Section: Results Illustrative Casementioning
confidence: 99%